2017
DOI: 10.1177/1010428317692261
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of microRNA-21 via locked nucleic acid-anti-miR suppressed metastatic features of colorectal cancer cells through modulation of programmed cell death 4

Abstract: Colorectal cancer is among the most lethal of malignancies, due to its propensity to metastatic spread and multifactorialchemoresistance. The latter property supports the need to identify novel therapeutic approaches for the treatment of colorectal cancer. MicroRNAs are endogenous non-coding small RNA molecules that function as post-transcriptional regulators of gene expression. Recently, programmed cell death 4 has been identified as a protein that increases during apoptosis. This gene is among the potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 50 publications
0
28
0
Order By: Relevance
“…It has been demonstrated that miR-21 promotes tumor cells proliferation and migration by down-regulating the expression of the sec23a protein[ 79 ]. The inhibition of miR-21 suppresses the metastasis of colorectal tumor cells by regulating programmed cell death 4[ 98 ]. In a miR-21 knockout mouse model, expression of proinflammatory and procarcinogenic cytokines was decreased, suggesting that miR-21 deficiency promotes the apoptosis of tumor cells by suppressing STATA3 and Bcl-2 activation[ 99 ].…”
Section: Prevention Strategies That Target F Nucleatummentioning
confidence: 99%
“…It has been demonstrated that miR-21 promotes tumor cells proliferation and migration by down-regulating the expression of the sec23a protein[ 79 ]. The inhibition of miR-21 suppresses the metastasis of colorectal tumor cells by regulating programmed cell death 4[ 98 ]. In a miR-21 knockout mouse model, expression of proinflammatory and procarcinogenic cytokines was decreased, suggesting that miR-21 deficiency promotes the apoptosis of tumor cells by suppressing STATA3 and Bcl-2 activation[ 99 ].…”
Section: Prevention Strategies That Target F Nucleatummentioning
confidence: 99%
“…MicroRNAs to target PDCD4 mRNA also may be a useful tool for the upregulation of PDCD4. Among them, nucleotide anti-mir21 drugs inhibit colon cancer cell metastasis up-regulating PDCD4-protein levels in in vitro experiments [100]. The anti-mir21 drug has already cleared phase 1 clinical trial in Polycystic kidney disease including Alport syndrome patients [101].…”
Section: Clinical Aspectsmentioning
confidence: 99%
“…miR-622, which is overexpressed in CRC tissues and cell lines, affects metastasis and invasion of CRC cells by regulating DYRK2 and its downstream signaling pathways 29 . Nedaeinia et al 30 transfected LS174T human colorectal adenocarcinoma cells with locked nucleic acid (LNA)-anti-miR-21 in vitro to determine the effect of miR-21 in cell growth and colony formation. At the same time, they constructed the LS174T cell chick embryo chorioallantoic membrane (CAM) module.…”
Section: Therapeutic Potentials Of Mirnasmentioning
confidence: 99%